A Severe case of antiphospholipid syndrome coexisting with systemic lupus erythematosus with major cardiovascular complications: a case report - Bińczyk, Wiktoria; Siudek, Bartosz; Dróżdż, Olgierd; Brzozowska, Patrycja; Nowińska, Bianka; Lissak, Karina; Sokolik, Renata (Quality in Sport, 2024)
Systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS) are autoimmune diseases that frequently coexist, complicating clinical management due to the compounded risks of systemic inflammation and thromboembolism. We present a case of a 52-year-old female with SLE and APS, initially diagnosed after a pulmonary embolism in 2015. Her medical history includes recurrent anemia, hyperlipidemia, hypertension, and two myocardial infarctions treated with angioplasty and stenting. Despite treatment with hydroxychloroquine, methylprednisolone, methotrexate and apixaban (later switched to warfarin), the patient experienced severe disease flare-ups and cardiovascular complications, prompting consideration for biologic therapy with anifrolumab. This case study illustrates the difficulties associated with the management of concurrent SLE and APS. It is clear that early diagnosis, vigilant monitoring, and aggressive management of both autoimmune and cardiovascular risks are essential to improve patient outcomes.